Growth performance and biochemical composition of Tetradesmus obliquus (Turpin) M.J. Wynne in media with different nitrogen concentrations - Rıza Akgül (Ciência Rural, 2024)
ABSTRACT: Microalgae have a great potential to change their metabolism pathway under stress condition, and nitrogen deficiency is an effective technique for maximizing lipids synthesis. This study focus on the growth performance, and biochemical composition of Tetradesmus obliquus (Turpin) M.J. Wynne cultured in different nitrogen concentrations (BG 11-Blue-Green Medium, 50% N+, 50% N-, 75% N+, 75% N-). Specific growth rate and protein content of T. obliquus decreased with nitrogen deficiency, but its lipid content was increased. Maximum specific growth rate (0.20-0.21) and protein content (47.82%, 47.62% DW-dried weight) values were obtained in 75% N+, 50% N+ medium. The highest lipid percentage was obtained in 50% N- medium. The biochemical composition of T. obliquus changes based on nitrogen concentration. Polyunsaturated fatty acids (PUFAs) are more abundant (49.69%) in this microalga under deficient nitrogen. To obtain more lipid and PUFAs in T. obliquus, N deficiency is an effective method, but it is not applicable to protein content. T. obliquus can be used as an alternative nutritional supplement with its high PUFAs content. Since different results are obtained from species to others in such studies, culture conditions should be determined for each species and according to the desired item.